Homologous Recombination Subpathways: A Tangle to Resolve - Elbakry, Amira; Löbrich, Markus (Frontiers in Genetics, 2021)
Homologous recombination (HR) is an essential pathway for DNA double-strand break (DSB) repair, which can proceed through various subpathways that have distinct elements and genetic outcomes. In this mini-review, we highlight the main features known about HR subpathways operating at DSBs in human cells and the factors regulating subpathway choice. We examine new developments that provide alternative models of subpathway usage in different cell types, revise the nature of HR intermediates involved and reassess the frequency of repair outcomes. We discuss the impact of expanding our understanding of HR subpathways and how it can be clinically exploited.